From Traditional to Digital: Exploring the Online Marketing Transformation of Culinary Micro, Small, and Medium Enterprises (MSMEs) in Karawang Indonesia - Maulana, Fakhry Reza (HM Publisher, 2024)
The rapid growth of digital technologies has revolutionized the way businesses operate, particularly for micro, small, and medium enterprises (MSMEs) in the culinary sector. This study investigates the online marketing transformation of culinary MSMEs in Karawang, Indonesia, exploring the strategies they employ, the challenges they face, and the impact of digitalization on their business performance. The study also examines the influence of the marketing mix (product, price, place, and promotion) on these businesses and how they leverage e-commerce platforms to reach a wider audience. The study also employs a SWOT analysis to understand the internal and external factors affecting these MSMEs. The research adopts a mixed-methods approach, combining qualitative and quantitative data collection techniques. In-depth interviews were conducted with owners and managers of culinary MSMEs in Karawang to gain insights into their online marketing practices and experiences. Additionally, a survey was administered to a larger sample of culinary MSMEs to gather quantitative data on their online marketing adoption and outcomes. The data analysis involved thematic analysis for qualitative data and descriptive and inferential statistics for quantitative data. The findings reveal that culinary MSMEs in Karawang are increasingly embracing online marketing tools and platforms, such as social media, e-commerce marketplaces, and food delivery apps. The adoption and utilization of these tools vary across different types of MSMEs, with larger and more established businesses demonstrating a higher level of digital maturity. The study also identifies several challenges faced by MSMEs in their online marketing efforts, including limited digital literacy, lack of resources, and intense competition. The results also highlight the importance of adapting the marketing mix to the online environment and the positive impact of e-commerce adoption on business performance. The SWOT analysis further reveals the strengths, weaknesses, opportunities, and threats faced by culinary MSMEs in their online marketing transformation. The online marketing transformation of culinary MSMEs in Karawang is an ongoing process, with both opportunities and challenges. While digital technologies offer significant potential for business growth and expansion, MSMEs need to overcome various obstacles to fully leverage these tools. The study provides valuable insights for policymakers, industry practitioners, and academics to support the digitalization of MSMEs in the culinary sector and promote their sustainable development.